Report of deputation to Minister of Health on "A National Health Service"...
1945-03 1945 1940s 8 pages - 2 - There would, however, be based upon the medical teaching schools and universities, an advisory body covering the regions described as the natural hospital regions, which would be concerned in the formation of the plan and would have its right to comment on the plan. The Minister would be bound not to approve the plan made by the 35 planning areas until he had considered the comments made from the regional point of view and from the point of view of co-ordinating the plans of the planning areas in the region. Those two changes were likely to arise. The statutory duty to prepare and submit a plan would be placed on the planning councils for 30 to 35 areas, democratically constituted, but with observations being made and with the right to comment at the regional level. A further point was the extent to which hospital provision was voluntary, which varied very greatly from one area to another. The Area Planning Council would have to plan many things besides hospitals. It would have to deal with dental service, nursing service and so on, and indeed would have to consider the strength of the general practitioner service in the area, and consequently it would probably be right that, though the Planning Council was responsible for submitting the general plan to the Minister for approval, the initial draft of the hospitals plan would probably be prepared by a special hospitals body - not a body which would make the plan, but one which would formulate proposals to be submitted to the Council. On dentistry, Mr. Willink continued, the White Paper was pessimistic and there were grounds for pessimism. Since the debates in the house the Interim Report of the Committee on Dentistry had been issued advocating a comprehensive dental service in spite of the shortage there would be for some time. They were hopeful therefore that they would be able to go forward more courageously on the dental side than the White Paper indicated. Mr. Johnstone said that there were two points upon which the set-up in Scotland was likely to differ from the set-up in England and Wales due largely to the geographical and population differences. For example Scotland proposed, as in the White Paper that for an experimental period the Health Centres which were going to be used by the General Practitioner Service should be started centrally, not by local authorities but by the Department of Health for Scotland with powers to delegate those centres and powers to the local authorities as and when suitable afterwards. They believed that in that way they could get the health centres into operation more speedily from the central authority without the difficulties inherent in the present local authority administration. The other point was that they proposed to adhere to the White Paper proposals to have Joint Hospital Boards formed by combination of joint local authorities to ensure an adequate hospital. and consultant service in all areas - all this to be under the planning arrangements for the wider areas. They felt that the present local authority boundaries were much too small to have adequate consultant and hospital services provided. They proposed to have joint hospital boards and suitable area arrangements to provide those services. With those two differences, the arrangements for Scotland would be the same as Mr. Willink had described for England and Wales. Mr. Allen said that the deputation included three representatives of the Medical Practitioners' Union which was associated with the T.U.C. There were some points that the deputation would like to put to the Minister and on which they would be glad to have some measure of assurance. 292/847/3/118